1976
DOI: 10.1111/j.1476-5381.1976.tb08627.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism by Some Antihistamines of the Amino Acid‐evoked Responses Recorded From the Lobster Muscle Fibre and the Frog Spinal Cord

Abstract: I The effects of some antihistamines on the lobster muscle fibre and the frog spinal cord were investigated using intracellular and extracellular recordings, respectively.2 On lobster muscle, histamine Hl-blockers reversibly antagonized responses to bath-applied glutamate, aspartate and quisqualate but not responses to y-aminobutyric acid (GABA). Iontophoretic glutamate potentials were also reduced. Histamine (up to 1 mM) had no effect on this preparation.3 The Hl-antagonists produced a small increase in muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Depolarization induced by histamine is likely due, at least in part, to the presence of histaminergic receptors on spinal motoneuron membranes, as suggested by our experiments where synaptic transmission was blocked. This has been previously reported for H 1 and H 2 receptors in the spinal cord (Constanti & Nistri, ; Wu et al, ). Interestingly, the extent of depolarization in the presence of TTX was lower than in physiological solution, indicating that most of the effect is indirect, probably due to recruitment of different neurotransmitters, such as glutamate (Garduño‐Torres, Treviño, Gutiérrez, & Arias‐Montaño, ), acetylcholine (Bacciottini et al, : Munari, Provensi, Passani, & Blandina, ), noradrenaline (Bealer, ), and serotonin (Threlfell et al, ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Depolarization induced by histamine is likely due, at least in part, to the presence of histaminergic receptors on spinal motoneuron membranes, as suggested by our experiments where synaptic transmission was blocked. This has been previously reported for H 1 and H 2 receptors in the spinal cord (Constanti & Nistri, ; Wu et al, ). Interestingly, the extent of depolarization in the presence of TTX was lower than in physiological solution, indicating that most of the effect is indirect, probably due to recruitment of different neurotransmitters, such as glutamate (Garduño‐Torres, Treviño, Gutiérrez, & Arias‐Montaño, ), acetylcholine (Bacciottini et al, : Munari, Provensi, Passani, & Blandina, ), noradrenaline (Bealer, ), and serotonin (Threlfell et al, ).…”
Section: Discussionsupporting
confidence: 86%
“…Four metabotropic histamine receptors have been described in the CNS (H 1‐4 ; Haas et al, ), and are also found in spinal tissue (Taylor, Yaksh, & Richelson, [for H 1 subtype]; Murakami, Sun‐Wada, Matsumoto, Wada, & Futai, [for H 2 ]; Cannon et al, [for H 3 ]; Strakhova et al, [for H 4 ]). The effects of H 1 and H 2 receptor activation on spinal motoneurons have been described (Constanti & Nistri, ; Taylor et al, ; Saito et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is conceivable that the conductance changes associated with NMDA-receptor activation are more susceptible to subtle changes in membrane potential that may have been induced by pyrilamine. In this regard, it is of interest that Constanti and Nistri (1976) reported that pyrilamine altered conductance and produced small changes in the resting membrane potential of lobster muscle fibers. In addition, it is possible that the NMDA receptor-ionophore complex is more susceptible to a non-competitive blockade by pyrilamine.…”
Section: Discussionmentioning
confidence: 99%
“…Electrotonic potentials were displayed on an oscilloscope and recorded on a chart recorder. In some experiments, a second voltagerecording electrode was introduced at the tendonend of the same fibre in order to calculate the membrane conductance (expressed as gmL, where g. is the conductance per unit length and L the fibre halflength) from 'short' cable theory (see Constanti, 1977 (Takeuchi & Takeuchi, 1964;Constanti & Nistri, 1976c; . However, following a bath-application of glutamate, the subsequent aspartate response was markedly enhanced and then declined progressively to a plateau as before.…”
Section: Methodsmentioning
confidence: 99%
“…Drugs were dissolved in this solution, adjusted to pH 7.6 and applied via the bathing medium. lontophoretic glutamate and aspartate potentials were obtained by the previously described method (Takeuchi & Takeuchi, 1964;Constanti & Nistri, 1976c; using standard double barrelled microelectrodes. One barrel was filled with 1 M L-Na glutamate (pH 8) and the second with 0.5 to 1 M L-Na aspartate (pH 8) (retaining currents were + 5 to + 30 nA).…”
Section: Methodsmentioning
confidence: 99%